Involvement of the Indonesian National Military (TNI) in Legislation about Anti-Terrorism - Satria Unggul Wicaksana Prakasa (Jember University Press, 2021)
Changes in the international humanitarian legal system in a global context have shifted, as the first war identified with an inter-state ceasefire. Today, the war party is not only a state but also the aftermath of the 9/11 tragedy marked by non-state war actors, a terrorist attack. In Indonesia, the issue of terrorism becomes a serious concern after the first Bali Bombing, the second Bali Bombing, and other terrorist tragedies. Lately, the discourse of TNI involvement in the eradication of terrorism in Indonesia through the formation of the Anti-Terrorism Act. According to the issue, the research problems are (1) TNI's authority elements to combat terrorism in the Indonesian legal system; (2) the International humanitarian law system regulates the involvement of the military on combating terrorism. The results of the study are (1) after the fall of New Order regime in 1998, the dual function of ABRI (Indonesian Armed Forces during Suharto's era) had dissolved, and this implied the limited authority of TNI to maintain the unitary state of the Republic of Indonesia (NKRI) sovereignty at the border. The authority of the TNI on combating terrorism, following Act No.34, 2004 section 7 articles (3) about TNI, mentions that the fight against terrorism deals with criminal methods. Except for war aggression, related to terrorism that threatens the State sovereignty and not against terrorism that occurs in the community on the Anti-Terrorism Act. If TNI wants to be involved in combating terrorism, it must be following the 1945 constitution, of which terrorism is part of non-international armed conflict, in which the power of command is in the hands of the President.